Updating and Refactoring Library Modules in IEC 61499 - Oberlehner, Michael; Zoitl, Alois (IEEE International Conference on Industrial Informatics (INDIN), 2024)
This paper proposes a novel library management system tailored for Cyber- Physical Production Systems (CPPSs) using the IEC 61499 standard. Focusing on software maintenance challenges in CPPSs, we introduce efficient updating and refac-toring operations for modularized type libraries. Our approach addresses the unique requirements of graphical development environments, enhancing the longevity and efficiency of software maintenance. The workflow of creating, maintaining, and up-dating library modules is outlined, along with conflict detection, error visualization, and potential refactoring/update operations. Additionally, we illustrate the architectural concept implemented as a prototype in an IDE. The implemented library management system demonstrates its practical application through a case study. This research contributes to the ongoing development of robust software maintenance practices in industrial automation systems.